Validation study of the Croatian version of the Edinburgh Postnatal Depression Scale (EPDS) - Nakić Radoš, Sandra (Array, 2013)
Validation studies established different cut-off points for the Edinburgh Postnatal Depression Scale (EPDS) in different countries. The aim of this paper was to validate the Croatian EPDS against DSM-IV-TR for major and minor depression. A community sample of 272 women was followed from pregnancy to six weeks postpartum. They filled out the EPDS and STAI and were diagnosed using the SCID-I-RV. At the 8/9 cut-off score the sensitivity of the EPDS was 77.3% and its specificity was 82.4%. The principal component analysis with oblique rotation resulted in two correlated oblique factors, reflecting depressive and anxiety symptoms. Since the scree plot indicated that a one-factor solution would be appropriate, it is advised to treat the scale as one-dimensional. The Croatian version of the EPDS is a valid screening instrument and can be used by health practitioners for PPD screening.